Extrapancreatic malignancies and intraductal papillary mucinous neoplasms of the pancreas - Benarroch-Gampel, Jaime (Baishideng Publishing Group Co., Limited, 2010)
Over the last two decades multiple studies have demonstrated an increased incidence of additional malignancies in patients with intraductal papillary mucinous neoplasms (IPMNs). Additional malignancies have been identified in 10%-52% of patients with IPMNs. The majority of these additional cancers occur before or concurrent with the diagnosis of IPMN. The gastrointestinal tract is most commonly involved in secondary malignancies, with benign colon polyps and colon cancer commonly seen in western countries and gastric cancer commonly seen in Asian countries. Other extrapancreatic malignancies associated with IPMNs include benign and malignant esophageal neoplasms, gastrointestinal stromal tumors, carcinoid tumors, hepatobiliary cancers, breast cancers, prostate cancers, and lung cancers. There is no clear etiology for the development of secondary malignancies in patients with IPMN. Although population-based studies have shown different results from single institution studies regarding the exact incidence of additional primary cancers in IPMN patients, both have reached the same conclusion: there is a higher incidence of extrapancreatic malignancies in patients with IPMNs than in the general population. This finding has significant clinical implications for both the initial evaluation and the subsequent long-term follow-up of patients with IPMNs. If a patient has not had recent colonoscopy, this should be performed during the evaluation of a newly diagnosed IPMN. Upper endoscopy should be performed in patients from Asian countries or for those who present with symptoms suggestive of upper gastrointestinal disease. Routine screening studies (breast and prostate) should be carried out as currently recommended for patient’s age both before and after the diagnosis of IPMN.